The readability of Malaysian medical tourism hospital websites - Ahmad Rauyani bin Ab Hamid (Kulliyyah of Languages and Management, International Islmic University Malaysia, 2017)
Effective health communication is important for making healthcare decisions. The Internet facilitates patients to learn about their treatments and diseases. More than 70 000 websites disseminate health information and 50 million Internet users seek health information online. The interaction between online health information seekers and healthcare providers has helped the growth of medical tourism industry. For medical tourists, one of their sources of information is hospital websites. Since patients are from different backgrounds, hospital websites should be written for the general public. This study was conducted to analyze the readability levels of Malaysian medical tourism hospital websites. Out of 44 hospital websites, 32 fulfilled the criteria for this study. SMOG Grading and Fry Readability Graph were used in this research. Using Fry and SMOG indices, it was found that these websites were written at a college level (Grade 15 and 16) and graduate training level (Grade 17 and 18). This suggests that these hospital websites were difficult and very confusing for the general public to comprehend.